Emergency care units and dimensions of accessibility to health care for the elderly - Giovana Aparecida de Souza Scolari; Leidyani Karina Rissardo; Vanessa Denardi Antoniassi Baldissera; Lígia Carreira
ABSTRACT Objective: to understand the conception of the elderly and their caregivers about the accessibility to health mediated by the service in Emergency Care Units. Methodo: a qualitative study conducted with 25 elderly patients and caregivers at Emergency Care Units in a city of Paraná, using Grounded Theory as a methodological reference. Results: According to the participants, the resources available in these services guarantee medical consultation and provide access to exams and medicines. Such resources have attracted patients and caused excess demand, which implies a set of compromising factors for the quality of care in these services. Final considerations: Investments in the restructuring of the care network, especially in primary care, with an increase in the number of consultations and the creation of a bond, can contribute to the emergency care units achieving the goal of access to qualified assistance to the elderly population.